The Maxwell-Boltzmann-Euler System with a Massive Scalar Field in All Bianchi Spacetimes - Raoul Domingo Ayissi; Norbert Noutchegueme; Hugues Paulin Mbeutcha Tchagna (Advances in Mathematical Physics)
We prove the existence and uniqueness of regular solution to the coupled Maxwell-Boltzmann-Euler system, which governs the collisional evolution of a kind of fast moving, massive, and charged particles, globally in time, in a Bianchi of types I to VIII spacetimes. We clearly define function spaces, and we establish all the essential energy inequalities leading to the global existence theorem.